Mothers' long‐run career patterns after first birth. (17th December 2015) - Frühwirth‐Schnatter, Sylvia; Pamminger, Christoph; Weber, Andrea; Winter‐Ebmer, Rudolf
Summary: Using Bayesian Markov chain clustering analysis we investigate career paths of Austrian women after their first birth. This data‐driven method allows characterizing long‐term career paths of mothers over up to 19 years by transitions between parental leave, non‐employment and different forms of employment. We classify women into five cluster groups with very different long‐run career trajectories after childbearing. We further model group membership with a multinomial specification within the finite mixture model. This approach gives insights into the determinants of long‐run outcomes. In particular, giving birth at an older age appears to be associated with very diverse outcomes: it is related to higher odds of dropping out of the labour force, on the one hand, but also to higher odds of reaching a high wage career track, on the other hand.